Virtual reality field trips as enabling environments for emotions and motivation in STEM education - McGivney, Eileen (Frontiers in Virtual Reality, 2025)
While emotions and motivation are key to the process of learning, typical classroom instruction lacks engagement of such affective dimensions of learning. Virtual reality (VR) technologies are powerful tools for engendering emotions and increasing intrinsic motivation that may enable science, technology, engineering, and math (STEM) learning that enhances learners’ affect. This study explored whether VR field trip experiences can be enabling environments for emotions and motivation in classroom learning. Thirty high school engineering students used VR experiences over four lessons, and mixed methods of surveys and interviews assessed what emotions they felt, the degree to which they were intrinsically motivated when learning with VR, and whether participating in the VR field trips changed their longer-term beliefs and motivation toward STEM. The results point to VR as an enabler of powerful emotions and high levels of intrinsic motivation, but that it may not have an effect on longer-term beliefs and attitudes.